Analisis Pendekatan Sustainable Growth Rate Dalam Mengukur Kinerja Keuangan Ksp Kopdit Pintu Air Cabang Kewapante, Desa Wairkoja, Kecamatan Waigete, Kabupaten Sikka - Kasimo, Fulgensius; Mitan , Wihelmina; Goo , Emilianus Eo Kutu (Jurnal Projemen UNIPA, 2025)
This research aims to analyze the financial performance of the Koperasi KSP Kopdit Pintu Air Kewapante Branch using the Sustainable Growth Rate (SGR) approach. This type of research is quantitative, using financial report data from KSP Kopdit Pintu Air Kewapante for the period of 2020 to 2024. The data is analyzed by calculating the Retention Ratio (RR), Return on Equity (ROE), and the Sustainable Growth Rate (SGR) value each year. The results show that the highest SGR value was achieved in 2021 at 11.04%, while the lowest value occurred in 2023 at 0.70%. Generally, the SGR trend showed fluctuations, with a decreasing trend after 2021. This is attributed to the decline in profitability and the cooperative's ability to retain earnings. This finding indicates that although KSP Kopdit Pintu Air Kewapante Branch has a fairly good financial performance, the sustainability of its financial growth needs to be anticipated with more optimal management strategies. This study proves that the Sustainable Growth Rate approach can be used as a quantitative measuring tool to assess the financial performance of cooperatives and provide a basis for strategic decision-making.